2023
DOI: 10.1038/s41577-023-00856-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeting IL-6 trans-signalling: past, present and future prospects

Abstract: Interleukin-6 (IL-6) is a key immunomodulatory cytokine that affects the pathogenesis of diverse diseases, including autoimmune diseases, chronic inflammatory conditions and cancer. Classical IL-6 signalling involves the binding of IL-6 to the membrane-bound IL-6 receptor α-subunit (hereafter termed ‘mIL-6R’) and glycoprotein 130 (gp130) signal-transducing subunit. By contrast, in IL-6 trans-signalling, complexes of IL-6 and the soluble form of IL-6 receptor (sIL-6R) signal via membrane-bound gp130. A third mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(96 citation statements)
references
References 217 publications
5
91
0
Order By: Relevance
“…The proposed FMDIA can easily realize the simultaneous detection of multiple proteins in a single sample because it only needs to add SA-MBs to separate all the different color-coded fluorescent microspheres for analysis. As a pleiotropic cytokine, interleukin-6 (IL-6) has been clinically associated with the occurrence of various diseases. , Previous studies have shown that IL-6 may serve as complementary hepatocellular carcinoma (HCC) markers and play a synergistic role with AFP in the early diagnosis of HCC. , Therefore, the capacity of the proposed FMDIA in the simultaneous detection of multiple proteins was explored using AFP and IL-6 as models, and the principle of simultaneous detection of multiple proteins is schematically displayed in Figure a. First, the capture antibodies of AFP were chemically conjugated to r-QDMS, and the capture antibodies of IL-6 were chemically conjugated to g-FMS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed FMDIA can easily realize the simultaneous detection of multiple proteins in a single sample because it only needs to add SA-MBs to separate all the different color-coded fluorescent microspheres for analysis. As a pleiotropic cytokine, interleukin-6 (IL-6) has been clinically associated with the occurrence of various diseases. , Previous studies have shown that IL-6 may serve as complementary hepatocellular carcinoma (HCC) markers and play a synergistic role with AFP in the early diagnosis of HCC. , Therefore, the capacity of the proposed FMDIA in the simultaneous detection of multiple proteins was explored using AFP and IL-6 as models, and the principle of simultaneous detection of multiple proteins is schematically displayed in Figure a. First, the capture antibodies of AFP were chemically conjugated to r-QDMS, and the capture antibodies of IL-6 were chemically conjugated to g-FMS.…”
Section: Resultsmentioning
confidence: 99%
“…As a pleiotropic cytokine, interleukin-6 (IL-6) has been clinically associated with the occurrence of various diseases. 38,39 Previous studies have shown that IL-6 may serve as complementary hepatocellular carcinoma (HCC) markers and play a synergistic role with AFP in the early diagnosis of HCC. 40,41 Therefore, the capacity of the proposed FMDIA in the simultaneous detection of multiple proteins was explored using AFP and IL-6 as models, and the principle of simultaneous detection of multiple proteins is schematically displayed in Figure 4a.…”
Section: Simultaneous Detection Of Multiplementioning
confidence: 99%
“…Third, tocilizumab blocks both the classical and trans-IL-6 signaling. 54 Whether this is the case for most of the variants used as proxies for IL-6R signaling (selected based on their effects on CRP, primarily reflecting classical signaling) remains untested. Animal studies have shown decreases in CXCL10 levels and T-cell recruitment after targeted pharmacological inhibition of the trans-signaling cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 depicts the concentration-dependent increase in cell viability caused by Lig therapy, in contrast to the suppressive impact seen with LPS treatment. Current investigations suggest that inflammatory cytokines, namely ICAM-1 (Buckley et al, 2022), interleukin-6 (IL-6) (Rose-John et al, 2023), and MCP-1 (Bittar et al, 2020), synthesized during the inflammatory response, can precipitate EC injury and dysfunction. ICAM-1, an indispensable adhesion molecule belonging to the immunoglobulin superfamily, typically exhibits diminished expression levels in a quiescent state but can be upregulated by various factors, thereby contributing to the adhesion of diverse leukocytes (Kucukal et al, 2020).…”
Section: Discussionmentioning
confidence: 99%